Chaihu Guizhi Ganjiang Decoction Ameliorates Pancreatic Fibrosis via JNK/mTOR Signaling Pathway - Cui, Lihua; Li, Caixia; Shang, Ye; Li, Dihua; Zhuo, Yuzhen; Yang, Lei; Cui, Naiqiang; Li, Yuhong; Zhang, Shukun (Frontiers in Pharmacology, 2021)
Pancreatic fibrosis is a pathological characteristic of chronic pancreatitis (CP) and pancreatic cancer. Chaihu Guizhi Ganjiang Decoction (CGGD) is a traditional Chinese medicine, which is widely used in the clinical treatment of digestive diseases. However, the potential anti-fibrosis mechanisms of CGGD in treating CP remains unclear. Here, we conducted a series experiments to examine the effect of CGGD on CP rat model and primary isolated pancreatic stellate cells (PSCs). The results revealed that CGGD attenuated pancreatic damage, decreased collagen deposition, and inhibited PSC activation in pancreas of CP rats. However, compared with CP group, CGGD had no effect on body weight, serum amylase and lipase. In addition, CGGD suppressed autophagy by downregulated of Atg5, Beclin-1 and LC3B and facilitated the phosphorylation of mTOR and JNK in pancreatic tissue and PSCs. Moreover, mTOR inhibitor rapamycin and JNK inhibitor SP600125, markedly attenuated CGGD drug-containing serum caused LC3B and collogen I downregulation in PSCs. In conclusion, CGGD attenuated pancreatic fibrosis and PSC activation, possibly by suppressing autophagy of PSCs through JNK/mTOR signaling pathway.